EXPLORING GEN Z'S INTEREST IN START-UPS: THE ROLE OF EMPLOYER BRANDING AND CORPORATE REPUTATION, WITH INNOVATIVE WORK BEHAVIOR AS A MODERATOR - Wahyuni Febriana; Poppy Alvianolita Sanistasya; Rosyid Nurrohman; Ummi Nadroh (Universitas Tulungagung, 2025)
This study aims to identify the job preferences of Generation Z in Samarinda and the factors that influence their interest in working for start-up companies. The research focuses on analyzing the influence of employer branding and corporate reputation on intention to apply, with innovative work behavior considered as a moderating variable. A quantitative approach was employed, using a questionnaire distributed to 105 Gen Z respondents in Samarinda. The results indicate that both employer branding and corporate reputation have a positive and significant effect on intention to apply. However, innovative work behavior does not moderate the relationship between employer branding and intention to apply. These findings highlight that a company's image and reputation play a crucial role in attracting Generation Z to job opportunities, particularly in the start-up sector. Therefore, companies are encouraged to develop appropriate strategies by understanding the work preferences of Generation Z, who are expected to dominate the labor market in the near future.